Blood cell disruption to significantly improve the Borrelia PCR detection sensitivity in borreliosis in humans. (July 2018) - Lacout, Alexis; Mone, Yves; Franck, Michel; Marcy, Pierre-Yves; Mas, Marie; Veas, Francisco; Perronne, Christian
Abstract: Lyme disease is the most frequently reported zoonotic tick-borne disease worldwide, and the number of infected humans is increasing. Lyme disease (or Lyme borreliosis) is an affection caused by the spirochete Borrelia burgdorferi, sensu lato . Lyme disease is also reported as a variety of misleading clinical symptomatologies. Infected patient's blood serology is the most currently test used for its diagnosis. However, serology has a low sensitivity, which ranges from 34% to 70%. Thus, there are numerous subsequent false-negative diagnoses despite an active clinical infection profile. Therefore, alternative and more sensitive techniques are required to detect the antigens or nucleic acids of Borrelia. Actually, the most appropriate methodological approach seems to be the polymerase chain reaction (PCR). However, PCR will detect the only "visible" part available of the targeted DNA presence in the blood of the infected patients. Consequently PCR alone will not be conclusive enough to reach the final diagnosis. Considering the ability of Borrelia to invade host cells, we hypothesize that a selective lysis of all blood cells should improve the diagnostic sensitivity of the detection of Borrelia by PCR in whole blood, and subsequently reduce the false-negative diagnostic rate, thus improving the patient's diagnosis and therapeutic management.